Mg-0.5Ca-4Zn-xCaCO3 (x=8, 10) Alloy Foams with Closed-Pore Structure Synthesized by Powder Metallurgy Process for Implant Applications - Aprilia Erryani; Franciska Pramuji Lestari; Joko Triwardono; Bunga Rani Elvira; Bintoro Siswayanti; Albertus Deny Hadi Setiawan (TEKNIK, 2023)
This work aims to synthesize Mg-0.5Ca-4Zn alloy foams using a CaCO3 foaming agent and a powder metallurgy (PM) process. Mg-0.5Ca-4Zn-xCaCO3 (x=8, 10 wt.%) alloy precursors were prepared by mixing Mg, Ca, and Zn metal powders with CaCO3 granules, compacting, and then sintering at various temperatures (i.e., 650, 675, and 700 °C) for 5 hours in an argon atmosphere. The pore morphology was observed by scanning electron microscopy (SEM), and the phase formation was analyzed using X-ray diffractometry (XRD). The density and porosity were evaluated using an Archimedes test (ASTM B311-93). The compressive strength was examined using a universal testing machine (UTM) with a constant crosshead speed of 1.3 mm/min (ASTM D695-02). SEM observation reveals the formation of pores with a closed-cell type structure in all alloy compositions. Increasing either the CaCO3 content or sintering temperature results in an increase in porosity and pore sizes but a decrease in compressive strength. The maximum porosity of 43.208% was obtained in the alloy foam with 10 wt.% CaCO3 sintered at 700 °C; the foam exhibits a compressive strength of 52.9 MPa, close to cancellous bone.